2007
DOI: 10.1097/cco.0b013e3281a3c0ba
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factors: finding the right indication

Abstract: Consistent clinical practice guidelines based on multiple randomized control trials and meta-analyses should further guide the appropriate and cost-effective use of these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…32 This finding has potential therapeutic implications, as it might be possible to reduce doses of growth factors and, consequently, the risk of adverse effects such as cancer. 33,34 However, further specific studies on the vascular niche are needed to investigate in depth its structure and mechanisms linked to PTH activity.…”
Section: Discussionmentioning
confidence: 99%
“…32 This finding has potential therapeutic implications, as it might be possible to reduce doses of growth factors and, consequently, the risk of adverse effects such as cancer. 33,34 However, further specific studies on the vascular niche are needed to investigate in depth its structure and mechanisms linked to PTH activity.…”
Section: Discussionmentioning
confidence: 99%
“…& CMF, with oral cyclophosphamide, was shown equally effective to AC and is an acceptable non-anthracycline containing chemotherapeutic option [72], but it is not less toxic in older breast cancer patients [13,21,73]. Doses should not be reduced, however, because reduction in relative dose intensity of adjuvant chemotherapy regimens results in worse outcomes [74]. & CALGB trial of monotherapy, with capecitabine 2,000 mg/m 2 are less strongly hormone receptor positive and higher grade so are less sensitive to endocrine therapies and more sensitive to chemotherapy [77,78].…”
Section: Hormone Receptor Negative Breast Cancermentioning
confidence: 97%
“…Granulocyte-colony stimulating factor (G-CSF) is a member of the hematopoietic growth factor family, which orchestrates the proliferation, differentiation, and survival of hematopoietic progenitor cells [8]. However, growing evidence has suggested that G-CSF also has important nonhematopoietic functions in other tissues including nervous tissues.…”
Section: Introductionmentioning
confidence: 99%